Chemistry the molecular science - Moore, John W. (Thomson Brooks/Cole, 2008)
This popular and easy-to-read text gives you the solid foundation you'll need for success in every science and engineering course you take. Every "Problem-Solving Example" includes a "Strategy and Explanation" section, which clearly describes the strategy and approach chosen to solve the problem. Success in your course is within your grasp with CHEMISTRY: THE MOLECULAR SCIENCE, Third Edition.